A feasibility study of a dedicated senior citizens area in the Quezon City Public Library main branch - Precilla, Peter Joseph A.; Obille, Kathleen Lourdes B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2011)
This thesis looked at the Quezon City Public Library Main Branch and evaluated its budget, resources, and programs to see if it could sustain a dedicated area catered to the needs of its elderly population. The needs and interests of seniors in Quezon City are also looked at in order to see what improvements should be implemented. The purposes of this study are to improve the quality of services given to this age group and increase the number of senior citizens who visit the QCPL.
Through the use of interviews with staff librarians in the QCPL, the study found out the current status of the library's collection and its staff, their annual budget with allocation, and their annual number of visitors. Meanwhile, using a questionnaire, the research was able to determine among fifty Quezon City senior citizens their current needs from a public library, the improvements and programs they want, and how to entice more elders to visit the QCPL.
The needs and interests of seniors that can be addressed by the QCPL are first, the addition of senior-only programs that not only enhance their skills, but also let them engaged with other seniors. Second, devote areas that can be for comfortable or casual reading and add appropriate collections. Third, enhance the seniors' skills in adapting to technology as some of our senior citizens are not computer-savvy. Fourth, devote staff that can enrich the senior's user experience in the library by giving then guided tours or one-on-one training. The proposal given in this study consists of /these four options.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Public libraries -- Philippines -- Quezon City; Older people -- Services for -- Philippines -- Quezon City